Heavy metals removal from industries wastewater by using seaweed through biosorption process - Suriani, Abdullah (2010)
One of the systems in treatment the heavy metals in industrial waste is by using the seaweed through the biosorption process. Biosorption using brown seaweed is most applicable method. In this study, biosorption of Cooper, Ferum and zinc were investigated. The industrial wastewater samples chosen are from industry of KNM, ASTURI and PPSC. All these industries are contributed in Metal manufacturing ang cleaning process. Comparing on those three industries, KNM showed the impressive absorption of heavy metals because of their high concentration of heavy metals in wastewater. These heavy metals have been effectively removed from very dilute solutions by the dried biomass of some brown marine seaweed Ecklonia maxima, which is 77 % of ferum, 51 % of Zinc, 29 % of Copper in industrial wastewater form industry of KNM was removed successfully. Besides, metals removal efficiency of the adsorbent was investigated as a function of different absorption parameters. From the Atomic Absorption Spectrometer (AAS) indicated the optimum of biosorption process was 180 minute of contact time, pH 5, 1.5 % of adsorbent dose, and 600 im of adsorbent particle size used for biosorption process. The analysis of biosequestering capacity of different seaweed to different metals and their suitability for bioremediation under the influence of effluent is discussed. Definitely, this dilute solution used as a control solution for guiding the real sample of industrial wastewater which applicable in environmental remediation.